Low‐dimensional material supported single‐atom catalysts for electrochemical CO2 reduction. Issue 1 (28th March 2022) - Wang, Bingqing; Chen, Shenghua; Zhang, Zedong; Wang, Dingsheng
Abstract: Converting CO2 emissions to valuable carbonaceous chemicals/fuels under mild conditions provides a sustainable way to maintain carbon balance and alleviate the energy shortage. Low‐dimensional material (LDM) supported single‐atom catalysts (SACs) have been attracted significant attention for electrochemical CO2 reduction reaction (ECR) in recent years. This is mainly because integrating the single‐atoms and LDMs can inherit the advantages of themselves and the synergy effects between them are potential to enhance the ECR performance. In this review, we summarized the strategies for synthesizing LDM supported SACs for ECR, and different LDM supported SACs for ECR have been briefly introduced. Moreover, some optimization strategies for LDM supported SACs towards CO2 electroreduction are highlighted. At the end of this review, the perspectives and challenges of LDM supported SACs for ECR are provided. Abstract : In this review, we have systematically summarized the low‐dimensional material (LDM) supported single‐atom catalysts (SACs) for ECR, and the perspectives and challenges of LDM supported SACs for ECR are also provided.